VISUAL BASIC APPLICATIONS OF DATA PROCESSING SERVICES FOR PATIENTS IN CLINICAL AL-FALAH - Ahmad Rojafi; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This application program is designed to simplify the administration of the clinic of Al-Falah, because by using this application program registration activities of new and oldpatients will be rapidly carried out. Especially for old patients who forget to bringmedical card, a patient can quickly be served because of the program to find the patientdata is easily and quickly, the data can be easy on looking good with the patients' medicalrecord number or the name of the patient. Printing reports any available medical records,if necessary by a physician, physician data report, and report patient data each day.